Gautieria mianjin (Gomphales, Basidiomycota), a new species of false truffle from China - Yang, Kun L.; Yang, Zhu L.; Zhang, Ming; Wang, Geng-Shen; Liu, Xiao (Phytotaxa, 2023)
A new species of false truffle, Gautieria mianjin, collected from northwestern China, is described based on morphological and phylogenetic evidence. It is characterized by its irregularly subglobose basidioma in the size of 2.5–5 cm in diameter with brain-like to honeycomb-like gleba and subglobose to broadly ellipsoid basidiospores measured 11–14×10–12 μm with 10–14 longitudinal ribs.